2015
DOI: 10.4310/atmp.2015.v19.n3.a1
|View full text |Cite
|
Sign up to set email alerts
|

Horizon instability of extremal black holes

Abstract: We show that axisymmetric extremal horizons are unstable under scalar perturbations. Specifically, we show that translation invariant derivatives of generic solutions to the wave equation do not decay along such horizons as advanced time tends to infinity, and in fact, higher order derivatives blow up. This result holds in particular for extremal Kerr-Newman and Majumdar-Papapetrou spacetimes and is in stark contrast with the subextremal case for which decay is known for all derivatives along the event horizon. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
233
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(250 citation statements)
references
References 30 publications
14
233
1
2
Order By: Relevance
“…In [4] he showed moreover that, under the assumption of pointwise decay of solutions and their tangential derivatives along the event horizon in affine time v, second-order transversal derivatives even blow up as v → ∞. This blow-up phenomenon has been dubbed the "Aretakis instability" in the literature [33].…”
Section: Previous Results For the Linear Wave Equation On Black Hole mentioning
confidence: 99%
See 1 more Smart Citation
“…In [4] he showed moreover that, under the assumption of pointwise decay of solutions and their tangential derivatives along the event horizon in affine time v, second-order transversal derivatives even blow up as v → ∞. This blow-up phenomenon has been dubbed the "Aretakis instability" in the literature [33].…”
Section: Previous Results For the Linear Wave Equation On Black Hole mentioning
confidence: 99%
“…Dafermos showed that black hole solutions approaching a subextremal ReissnerNordström solution along the event horizon 4 have a non-empty Cauchy horizon, beyond which the metric can be extended as a C 0 function. Moreover, under a lower bound assumption on the decay of the scalar field along the event horizon, transversal derivatives of φ and the L 2 loc norm of the Christoffel symbols of the metric blow up at the Cauchy horizon.…”
Section: Results For the Spherically Symmetric Einstein-maxwell-scalamentioning
confidence: 99%
“…In [4], he, moreover, proved the existence of conserved quantities, the Aretakis constants, along H + for solutions φ (that need not be axisymmetric). If non-vanishing, these constants constitute an obstruction to the decay of either φ itself or its transversal derivative.…”
Section: Linear Waves In the Exterior Region Of Extremal Kerrmentioning
confidence: 99%
“…In [22] the construction of r * from [32] is used to extend the local doublenull coordinates in M int to obtain a smooth, global Eddington-Finkelsteintype double-null foliation of M int ∩ {r > e 2 2M }, 4 such that the 2-surfaces S 2 u ,v = {u = u } ∩ {v = v } are diffeomorphic to 2-spheres and we, moreover, obtain quantitative bounds on the metric components in double-null coordinates (see Sect. 2.3).…”
Section: Double-null Coordinatesmentioning
confidence: 99%
“…[43]) if the NE family is a charged version of the zero-damping modes discussed recently in the context of rotating Kerr BHs [45]. It is also unclear if there is any relation between such long lived modes and the instability of exactly extremal geometries [46,47].…”
Section: Physical Review Letters 120 031103 (2018)mentioning
confidence: 99%